The IR-RF alpha-efficiency of K-feldspar - Kreutzer, Sebastian; Martin, Loïc; Dubernet, Stéphan; Mercier, Norbert (Radiation measurements, 2018)
Infrared radiofluorescence (IR-RF) of K-feldspar is an alternative luminescence dating approach to infrared luminescence (IRSL). The application of IR-RF on coarse grain K-feldspar untreated with HF requires knowledge of the IR-RF α-efficiency. We present IR-RF α-efficiency measurements performed on four natural fine grain (4-11μm) K-feldspar samples and test whether the α-efficiency is similar to that reported for IRSL on polymineral fine grain. The samples originate from Late and Middle Pleistocene aeolian sediment records in France and Germany. The fine grain fraction was obtained by crushing grains of diameter 90-200μm. The natural signal was reset by optical bleaching at 70°C using a solar simulator. The α-irradiation was carried out on a home-made α-irradiator, equipped with a 241Am source. For our irradiation setup, energy spectra were simulated using Geant4 to estimate the particle energy of the incident and exiting α-particles after passing a K-feldspar target. The α-flux induced IR-RF signals show a (super) linear dose-response up to 9.5×109 (integrated α-flux on the sample). The results indicate no significant difference between the IR-RF α-efficiency of the four samples. An averaged central Sα -value of 9.26±1.62 μGy/(103α cm−2) (corresponding a-value: 0.067±0.012) was obtained from 84 measurements of all four samples. Our results are similar to a-values reported for IRSL on polymineral fine grain. We finally discuss how the central Sα-value can be applied to calculate the β-equivalent α-dose rate of coarse grain mineral extracts.
Online verfügbar: 2. Mai 2018, Artikelversion: 24. Januar 2019
Gesehen am 27.03.2025